2018
DOI: 10.1088/1741-4326/aac444
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of runaway electron synchrotron spectra at high magnetic fields in Alcator C-Mod

Abstract: In the Alcator C-Mod tokamak, runaway electron (RE) experiments have been performed during low density, flattop plasma discharges at three magnetic fields: 2.7, 5.4, and 7.8 T, the last being the highest field to-date at which REs have been generated and measured in a tokamak. Time-evolving synchrotron radiation spectra were measured in the visible wavelength range (λ ≈ 300-1000 nm) by two absolutelycalibrated spectrometers viewing co-and counter-plasma current directions. In this paper, a test particle model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
(102 reference statements)
2
15
0
Order By: Relevance
“…The exact source of this discrepancy is not certain yet. In C-MOD and FTU, comparison with modeling has indicated that synchrotron damping is sufficient to explain the anomalously high measured damping [226][227][228].…”
Section: B Startup and Quiescent Runaway Electronsmentioning
confidence: 99%
“…The exact source of this discrepancy is not certain yet. In C-MOD and FTU, comparison with modeling has indicated that synchrotron damping is sufficient to explain the anomalously high measured damping [226][227][228].…”
Section: B Startup and Quiescent Runaway Electronsmentioning
confidence: 99%
“…The full spectral and angular calculation of synchrotron emission is available in SOFT. However, because the angular spread of synchrotron emission is quite small (∼1/γ, where γ is the relativistic factor), a "cone" model -where radiation is only emitted along the RE direction of motion -serves as an adequate approximation of the full angular formulation, as discussed in [5,10,32]. Additionally, the cone model significantly reduces computation time, which for all SOFT simulations used in this work was ∼3700 CPU hours in total.…”
Section: Synthetic Images From Softmentioning
confidence: 99%
“…Most recently, in Tinguely et al. (2018 a , b , 2019), synchrotron spectra, images and polarization data were analysed with the help of the synthetic diagnostic Soft (Hoppe et al. 2018 b ) in a series of Alcator C-Mod discharges, providing valuable constraints on runaway energy, pitch angle and radial density.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments of synthetic synchrotron diagnostics have allowed detailed analysis of experimental synchrotron data. Most recently, in Tinguely et al (2018aTinguely et al ( ,b, 2019, synchrotron spectra, images and polarization data were analysed with the help of the synthetic diagnostic SOFT (Hoppe et al 2018b) in a series of Alcator C-Mod discharges, providing valuable constraints on runaway energy, pitch angle and radial density. Full-orbit simulations have also recently provided deeper insight into observations of synchrotron radiation in three-dimensional magnetic fields (Carbajal & del Castillo-Negrete 2017;del Castillo-Negrete et al 2018).…”
Section: Introductionmentioning
confidence: 99%